The mediating role of achievement goal orientations on the associations between empowering/disempowering climates and the state of flow in young soccer players - Domínguez González, José Antonio; Morales-Sánchez, Verónica Odilia; Sanchez García, Carolina; Hernández-Mendo, Antonio; Reigal-Garrido, Rafael Enrique (Sage, 2025)
The motivational climate created by coaches influences athletes’ experiences of flow. Achievement goal orientations may help explain this relationship, acting as a key link between empowering or disempowering climates and athletes’ flow states. The purpose of this research was to analyse the mediating effect of motivational orientation (task and ego) on the relationships between empowering/disempowering motivational climate and the state of flow in a sample of young footballers. An associative and explanatory design was used to analyse the extent to which the athletes’ motivational orientation explained the association between the motivational climate created by the coaches and the state of flow. A total of 328 male adolescents, aged between 14 and 18 years (M = 15.83; SD = 1.38), who were affiliated with football teams in the city of Málaga (Spain) participated. Mediation analyses were performed using Model 4 of SPSS PROCESS v.4.1 software to test the indirect effects of motivational climate on flow through achievement goal orientations. The analyses highlighted statistically significant and positive relationships between the empowering climate and task-oriented motivation, as well as between the disempowering climate and ego-oriented motivation. Additionally, task orientation was more strongly associated with the state of flow and played a partial mediating role between the empowering climate and the state of flow. The results underscore the importance of promoting empowering climates in sports contexts due to their relationship with the promotion of task-oriented motivations and their impact on athletes’ states of flow.
https://openpolicyfinder.jisc.ac.uk/id/publication/10157?from=single_hit
Keywords: Futbolistas - Aspectos psicológicos; Psicología del deporte; Association football; Athlete well-being; Autonomy support; Motivation; Optimal psychological state; Task orientation